Cationic polymerization of vinyl ethers and p‐methoxystyrene by a benign initiating system: Silver salt/arylmethyl halide/dialkyl sulfide. Issue 6 (13th October 2015) - Lin, Li; Zhang, Guangyou; Kodama, Koichi; Shitara, Hiroaki; Hirose, Takuji
ABSTRACT: Three vinyl ethers (VEs: isobutyl vinyl ether, ethyl vinyl ether, and isopropyl vinyl ether) and an active styrene derivative, p ‐methoxystyrene (pMOS), were employed for cationic polymerization using a benign initiating system, AgClO4 /Ph2 CHBr/dialkyl sulfide. Choosing a sulfide with suitable nucleophilicity was important for achieving controlled polymerization. Additionally, selecting an appropriate reaction temperature based on monomer reactivity was also crucial for suppressing side reactions. Highly controlled polymerizations of VEs and pMOS were further confirmed by proton nuclear magnetic resonance ( 1 H NMR) and matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry (MALDI‐TOF‐MS). In addition, the coordination of the arylmethyl cation to the added base obviously influenced the initiation, as demonstrated by 1 H NMR analysis. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2016, 54, 861–870 Abstract : Cationic polymerization of vinyl ethers (VEs) and p ‐methoxystyrene was conducted using an ecofriendly initiating system containing silver perchlorate/arylmethyl halide/dialkyl sulfide. Well‐controlled polymerization behavior was demonstrated by 1 H NMR and MS spectroscopy. Appropriate reaction temperature and the coordination of dialkyl sulfide to arylmethyl cation were essential and their effects were investigated in detail by MS and 1 H NMR, respectively.